The Impact of Climate Change on Economic Growth in Africa: An Econometric Analysis - Rais, Imen; Tahtane, Mourad (Finance and Business Economies Review, 2022)
African economics are characterized by strong economic dependency on sectors highly vulnerable to climate change that may make it more susceptible to climate change. This study aims to investigate the effect of climate change on both short and long-run economic growth in Africa using a panel of 34 selected African countries for the period of 1971–2019. The study relies on a dynamic panel model with a multifactor error structure; we estimate the model through the cross-sectionally augmented autoregressive distributed lag (CS-ARDL) and the cross-sectionally augmented distributed lag (CS-DL) approaches. We find clear evidence that climate change is negatively associated with economic growth in both the short and long-run. We establish that a rise in the mean temperature change with one degree would significantly reduce the real GDP per capita in Africa by 1.68% (2.45%) in the short-run (long-run), respectively